HUBUNGAN SPATIO TEMPORAL URBAN HEAT ISLAND (UHI) DENGAN NILAI INDEKS VEGETASI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (Studi kasus : Kota Padang, Sumatera Barat) - rahmat hidayat; febriandi febriandi (JURNAL BUANA, 2025)
This research aims to: (1) To find out the variation of Normalized Difference Vegetation Index (NDVI) and Enchanced Vegetation Index (EVI) in Padang City (2) To find out how the spatio temporal variation in Padang City area (3) To find out the relationship between Urban Heat Island (UHI) and vegetation density index using Person Product Moment analysis in Padang City. The research used a quantitative approach with descriptive research type. The variables used in this study are vegetation density using NDVI and EVI analysis techniques. Surface temperature analysis using LST (Land Surface Temperature) analysis technique. The results of the study in 2013, 2019, and 2023 in Padang City had good vegetation density dominated by high vegetation density categories. Pearson Product Moment correlation shows vegetation density using NDVI and surface temperature affect UHI which has a strong correlation in 2013, 2019, and 2023. EVI correlation also has a strong correlation in 2013, 2019, 2023.